Quantitative precipitation forecast using NWP WRF-ANN model for hydrometeorological flood forecasting / Intan Shafeenar Ahmad Mohtar - Ahmad Mohtar, Intan Shafeenar (2023)
Flood forecasting accuracy is crucial for authorities so that they can make better plans. There are many variables involved to provide accurate flood forecasting. The case study area is at Kelantan River Basin, where it experiences the northeast monsoon. QPF from the NWP model was processed, analyzed and applied as an alternative to traditional rain gauge system to be the input to an integrated hydro-meteorological flood forecasting system. The direct QPF outputs from the WRF model with a horizontal resolution of 4 km x 4 km was validated against gauged rainfall measurements. The findings demonstrate that the WRF model have the ability to produce QPF for rainfall forecasting, though the accuracy is found to be not very satisfactory. In order to improve the accuracy, ANN model was applied which incorporates several WRF model products.